COST AND TIME EVALUATION WITH TIME COST TRADE OFF (TCTO) METHOD IN TIJ TUNNEL CONSTRUCTION (JOYOBOYO INTERMODA TERMINAL) - Triana, Masca Indra; Baharnur, Ahmad Zaenul; Mawaritza, Putri Suci (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2025)
Infrastructure development is one of the main indicators in supporting city development, especially in metropolitan areas such as Surabaya. One of the strategic projects being designed is the construction of a pedestrian tunnel that will connect the Joyoboyo Intermodal Terminal (TIJ) with the Surabaya Zoo (KBS). This study aims to optimize the cost and completion time of the project through a case study of the construction of a pedestrian tunnel between TIJ and KBS. Based on the contract's provisions, this project is scheduled to be completed within 156 calendar days, starting on May 30 2024, and ending on November 21, 2024. As an effort to optimize the cost and duration of project implementation, the Time Cost Trade Off (TCTO) approach is used. Through the application of this method, the results obtained that the addition of working time (overtime) for 3 hours per day on the work item of reinforced concrete walls with a thickness of 60 cm and concrete quality Fc'35 MPa (PC 450) is quite effective in accelerating project completion from 156 days to 145 days. In addition, the optimum cost generated is Rp14,116,469,946.62, which means a cost saving of Rp43,510,269.42 compared to the normal cost. From the analysis results, the project time efficiency is 0.31%.